Planning for the perfect storm: Perceptions of UK mental health professionals on the increasing impacts of climate change on their service users - Kimberly Croasdale; Kate Grailey; Neil Jennings; Joseph Mole; Emma L. Lawrance (Elsevier, 2023)
Introduction: Climate change poses a considerable risk of further increasing the world's mental health burden. The ways that, and extent to which, climate change is affecting mental health service users is poorly known. Mental health professionals (MHP)s' views on the nature of climate-related distress and the need for specialist training to support service users is undetermined globally. Methods: A questionnaire survey was disseminated to an opportunity sample of MHPs based in the United Kingdom (UK). It investigated whether MHPs perceived that the number of service users mentioning climate change as affecting their mental health or emotional distress had increased in the five years prior to 2021, and if they believe it will increase further. The survey explored MHPs' perceptions of the influence of climate change on service users' mental health needs, if they perceive this to be rational, and if they feel adequately prepared to manage climate change related mental health problems or emotional distress. Results: We surveyed 75 MHPs, including professionals in psychotherapy (38), psychology (19), psychiatry (6). MHPs reported a significant increase in the perceived prevalence of mental health problems or emotional distress related to climate change, believing this increase will continue. MHPs reported a range of impacts on service users due to climate change, typically viewed as a rational response. MHPs felt equipped to manage the consequences of climate change but would benefit from specific training. Conclusions: Our results indicate an increasing incidence of climate-related emotional distress among service users as perceived by MHPs. The expectation among professionals is that this service need is here now but will continue to increase in the future, with potential implications for the provision of training.